Górnik Polski . pismo Krajowej Komisji Koordynacyjnej Górnictwa NSZZ "Solidarność", no. 29, 1986 - Szczepański, Jarosław; Cieszewski, Jacek; Rajski, Wiesław; Sołowiej, Jerzy (KKK NSZZ "Solidarność", 1986)
Motto: "God bless you"